Simulation of pedestrian evacuation with blind herd mentality under adverse sight conditions. (June 2016) - Yue, Hao; Wang, Shuai; Jia, Xiaolu; Li, Juan; Shao, Chunfu
Pedestrian dynamics under adverse sight conditions is a difficult point in the field of pedestrian flow. In this paper, the simulation of pedestrian evacuation flow is carried out with blind herd mentality under adverse sight conditions. The pedestrian sight radius is introduced to describe adverse sight conditions, based on which blind following movement is adopted to describe the blind herd mentality of pedestrians in the door-invisible area. A special technology is introduced to compute the transition payoff in the dynamic parameter model to crystallize blind following movement, in which the concepts of choice vector, velocity vector, and direction similarity are introduced. Simulation results indicate that evacuation time under adverse sight conditions declines with increases in sight radius and gradually reaches a stable situation. It was found that evacuation time will rely on sight radius, initial density, and exit width. It was also observed that pedestrians blindly walk in herd-like patterns and crowd around the wall in the door-invisible area. Compared with the published model, the improved model is more effective in reducing evacuation time and dependence on sight radius. The extended model with internal layout and heterogeneous movement rules in a room is discussed as a possible future direction.